ANALISIS KEPUASAN PELANGGAN PRODUK UMKM PIZZA Sha-Ya DI LINGKUNGAN STIE RIAU PEKANBARU - Sundari, Rina (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
Hearing the word Pizza must have been familiar to the ears of society now. Pizza that used to be synonymous with upscale food, now no longer because of the mushrooming of UMKM products that sell different types of pizza with different variants and toping different, one of the products of UMKM that sell pizza is Pizza Sha-Ya. This research is to know the extent of customer satisfaction of Pizza Sha-Ya that exist in academic environment of STIE Riau. The number of samples taken as many as 30 people consisting of students / I, lecturers and employees of STIE Riau who ever consumed Pizza Sha-Ya. This research is descriptive qualitative